Greening the future: identifying and mitigating environmental hotspots in the MSME sector - a wall mixer case study - Singh, Jitender; Gupta, Sumit; Jagtap, Sandeep (Taylor & Francis, 2024)
In response to concerns about depleting natural resources, organisations are developing eco-friendly products and services. This study examines the role of manufacturing industries and services in sustainable resource utilisation, focusing on the Micro, Small, Medium Enterprises (MSME) sector, a significant contributor to global Gross Domestic Product (GDP). Using Life Cycle Assessment (LCA) methodology, the research identifies hotspots within the production processes of three companies manufacturing bathroom fittings, specifically the ‘Wall mixer’ component used in households and hotels. The study calculates In response to concerns about depleting natural resources, organisations are developing eco-friendly products and services. This study examines the role of manufacturing industries and services in sustainable resource utilisation, focusing on the MSME sector, a significant contributor to global GDP. Using Life Cycle Assessment (LCA) methodology, the research identifies hotspots within the production processes of three companies manufacturing bathroom fittings, specifically the ‘Wall mixer’ component used in households and hotels. The study calculates CO2 equivalents for each phase of the product lifecycle, identifying average gate-to-gate process values across the companies. This comparison reveals specific hotspots, with a significant one identified, leading to recommendations for industries to prioritise this issue for immediate energy savings. The primary focus is to establish an initial benchmarking system to reduce CO2 equivalents in cradle-to-gate or gate-to-gate systems. Implementing these measures is expected to reduce the carbon footprint, energy consumption, and raw material usage, ultimately enhancing profitability for the three companies. equivalents for each phase of the product lifecycle, identifying average gate-to-gate process values across the companies. This comparison reveals specific hotspots, with a significant one identified, leading to recommendations for industries to prioritise this issue for immediate energy savings. The primary focus is to establish an initial benchmarking system to reduce CO2 equivalents in cradle-to-gate or gate-to-gate systems. Implementing these measures is expected to reduce the carbon footprint, energy consumption, and raw material usage, ultimately enhancing profitability for the three companies.
Keywords: Sustainability; MSME’s; carbon dioxide equivalent; greenhouse gas emissions (GHGs); hotspot analysis